Inhibition of Listeria monocytogenes by Food-Borne Yeasts - Goerges, Stefanie (American Society for Microbiology, 2006)
Many bacteria are known to inhibit food pathogens, such as Listeria monocytogenes, by secreting a variety of bactericidal and bacteriostatic substances. In sharp contrast, it is unknown whether yeast has an inhibitory potential for the growth of pathogenic bacteria in food. A total of 404 yeasts were screened for inhibitory activity against five Listeria monocytogenes strains. Three hundred and four of these yeasts were isolated from smear-ripened cheeses. Most of the yeasts were identified by Fourier transform infrared spectroscopy. Using an agar-membrane screening assay, a fraction of approximately 4% of the 304 red smear cheese isolates clearly inhibited growth of L. monocytogenes. Furthermore, 14 out of these 304 cheese yeasts were cocultivated with L. monocytogenes WSLC 1364 on solid medium to test the antilisterial activity of yeast in direct cell contact with Listeria. All yeasts inhibited L. monocytogenes to a low degree, which is most probably due to competition for nutrients. However, one Candida intermedia strain was able to reduce the listerial cell count by 4 log units. Another four yeasts, assigned to C. intermedia (three strains) and Kluyveromyces marxianus (one strain), repressed growth of L. monocytogenes by 3 log units. Inhibition of L. monocytogenes was clearly pronounced in the cocultivation assay, which simulates the conditions and contamination rates present on smear cheese surfaces. We found no evidence that the unknown inhibitory molecule is able to diffuse through soft agar.